Cryptocurrency in The Perspective of Maqasid Al-Shariah - Wartoyo Wartoyo; Alvien Septian Haerisma (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2022)
This study explains the Islamic economic perspective on cryptocurrency, in this case, in the light of maqashid shariah. This research was a literature study and qualitative in nature. The data analysis applied a descriptive-analytical technique with a normative juridical approach to Islamic law. The results of this study conclude that cryptocurrency has a much greater element of mafsadah than maslahah. It is an investment commodity rather than a currency with a very high level of risk and volatility that reflects the mafsadah. This is the attraction of a new investment model because it only follows the trend of global market developments that are far from the function and benefits of currency in the perspective of Islamic economics.